Does motivation matter? – The relationship between teachers’ self-efficacy and enthusiasm and students’ performance - Mahler, Daniela; Großschedl, Jörg; Harms, Ute (PLOS ONE, 2018)
Knowledge and motivation of a teacher are two unchallenged, essential characteristics for successful education. Whilst the relevance of teachers' professional knowledge for successful students' learning has been studied in a sophisticated manner for years, the meaning of teachers' motivational orientations for students' performance still lacks a differentiated consideration. This construct is conceptualized by three domains: (1) self-efficacy, (2) subject-specific enthusiasm, and (3) enthusiasm for teaching the subject. Motivational orientations overall have shown to be relevant predictors of students' learning. However, there are several dimensions of motivation and their relative importance remains unclear. Our study goes beyond the available findings by considering in detail each of the three domains' relations to students' performance. Thus, we aim to further contribute to the clarification of the predictors of students' performance in school teaching. For this purpose, we conducted a study with 48 biology teachers and their 1036 students. To assess the three domains of teachers' motivational orientations, we applied paper and pencil tests. Concept maps and paper and pencil tests were used to measure students' performance. By specifying multilevel structural equation models, we examined the relationship between the domains of teachers' motivational orientations and the performance of the students. Our results reveal no relationship between teachers' self-efficacy and students' performance, but a significant positive relationship between the latter and teachers' subject-specific enthusiasm. Moreover, our results show a positive trend in the relationship between enthusiasm for teaching the subject and students' performance. The results provide a differentiated picture about the importance of motivational orientations for the characterisation of an effective teacher. We discuss our findings in terms of possible effect mechanisms and their relevance for further research on teacher motivation and the improvement of teacher education programmes.